Stimulation of the enterprise structures which are carrying out research and development - L. A. Akhmetov; A. O. Ryzhkov (Путеводитель предпринимателя)
The article analyzes the development of incentive mechanism of granting tax benefits to enterprises carrying out research and development (R & D). Identified gaps mediated stimulation and propose measures aimed at improving tax policy in terms of stimulating the development of business organizations that perform research and development.